Peran Literasi Keuangan dalam Memoderasi Hubungan Antara Modal Usaha dan Digital Marketing Terhadap Kinerja UMKM - Budi Riyanti; Hardi Utomo; Rindu Ajeng Wiganingtyas (Pusat Riset dan Inovasi Nasional, 2026)
The Indonesian government has supported MSMEs through initiatives such as business loans, training, and digitalization programs to enhance competitiveness. However, many MSMEs still struggle to manage capital effectively and to utilize digital marketing technology due to low financial literacy and limited digital skills. This study aims to analyze the impact of venture capital and digital marketing on MSME performance and to examine the role of financial literacy in moderating the relationship between venture capital and digital marketing. The research population consisted of 26.601 MSMEs in Salatiga, and the sample size was determined using the slovin formula, resulting in 100 respondents. The analytical tool used was Moderating Structural Equation Modeling (PLS) with a moderation model. Research variables were operationalized using 17 indicators. The results indicate that venture capital positively affects MSME performance, while digital marketing has no significant effect. Financial literacy morerates the relationship between venture capital and MSME performance, but does not moderate the relationship between digital marketing and MSME performance. Practically, the findings provide regulatory implications: 1) the government should collaborate with banking institutions to create regulations that facilitate easier access to capital for MSMEs, and 2) the government should expand digital marketing training and, if necessary, offer mentoring to ensure MSMEs can optimally implement digital marketing, thereby supporting the goal of “Digital Indonesia 2025”